Supply chain of Andean grains for exportation to the United States - Guardián-Sedano, José Enrique (2019)
Peruvian Andean grains have potential both locally and internationally; however, in recent years, prices have decreased because of rejected shipments due to quality noncompliance. The development of an optimal supply chain would benefit all its members, facilitate the flow of products and information, foster better compliance with customers, requirements, and promote innovation for developing better products.